Synthesis and in vitro Cytotoxicity of Novel Platinum(II) Complexes - Wang, Q.K.; Pu, S.P. (Asian Journal of Chemistry, 2015)
Four novel multinuclear platinum(II) complexes with 1R,2R-diaminocyclohexane, Pt-S coordination bond and dicarboxylic acid ion chains as bridges, were designed, prepared and spectrally characterized. The in vitro cytotoxicities of the new compounds were evaluated against HL-60, SMMC-7721, A-549, MCF-7 and SW480 human tumor cell lines by MTT assay. The results indicated that all compounds showed cytotoxicity, particularly, complex 1a, which has oxalic acid ion as a bridge, showed comparable anticancer activity to oxaliplatin against HL-60 and SMMC-7721.